Photochromic bi-naphthopyrans. (February 2015) - Aiken, Stuart; Gabbutt, Christopher D.; Heron, B. Mark; Kolla, Suresh B.
Abstract: A series of novel 3-aryl-(3, 3-diaryl-3 H- naphtho[2, 1- b ]pyran-8-yl)-3 H -naphtho[2, 1- b ]pyrans has been accessed from 6-bromo-2-naphthol via a four step transformation. Acylation of the dianion derived from the treatment of 6-bromo-2-naphthol with n -butyllithium with Weinreb amides and subsequent reaction with a 1, 1, -diarylprop-2-yn-1-ol gave 8-aroyl-3 H -naphtho[2, 1- b ]pyrans in good yield. Addition of lithium trimethylsilylacetylide to the foregoing 8-aroylnaphthopyrans proceeded smoothly with base-mediated desilyation to afford the target bi-naphthopyrans upon acid-catalysed reaction with 2-naphthol. Preliminary evaluation of the photochromic response of the new bi-naphthopyrans revealed reversible independent naphthopyran ring-opening leading to a complex photochromic signature. Graphical abstract: Novel 6-aroyl-2-naphthols have been used as building blocks to access a series of photochromic bi-naphthopyrans. Highlights: 6-Aroyl-2-naphthols have been synthesized using Weinreb amide chemistry. Acid-catalysed reaction of 6-aroyl-2-naphthols with diarylpropynols affords 8-aroylnaphthopyrans. Bi-naphthopyrans have accessed from 6-aroyl-2-naphthols by a three step transformation. The 8-aroyl group induces a bathochromic in λ max of the irradiated 8-aroylnaphthopyrans. The bi-naphthopyrans exhibit a complex temperature dependent photochromic signature.